2010
DOI: 10.1002/jsfa.4023
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of extracts from the aerial part of Coriandrum sativum L. on LPS-induced inflammatory responses in murine RAW 264.7 macrophages

Abstract: Our data demonstrated that aerial parts of CSEE have a strong anti-inflammatory property which inhibits pro-inflammatory mediator expression by suppressing NF-kappaB activation and MAPK signal transduction pathway in LPS-induced macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Wu ve arkadaşlarının 2010 yılında yaptığı bir çalışmada, kişnişin toprak üstü kısımlarının etanollü ekstrelerinin antienflamatuvar özellikleri, olası etki mekanizmaları incelenmiş ve kişniş yaprakları ile saplarının NO ve prostaglandin üretimini azalttığı gözlenmiştir (73). Özbek ve arkadaşlarının yaptığı bir çalışmada, kişniş uçucu yağ ekstresinin farelerde LD 50 dozu düzeyinin 2,257 mL/kg olarak hesaplandığı, sıçanlarda Carrageenan'la oluşturulmuş sağ arka pençe ödemi modelinde indometazinden daha zayıf bir antienflamatuvar aktivite gösterdiği ve bu etkinin uçucu yağı oluşturan komponentlerden en az ikisi tarafından meydana getirildiği bildirilmiştir (74).…”
Section: Antienflamatuvar Etkiunclassified
“…Wu ve arkadaşlarının 2010 yılında yaptığı bir çalışmada, kişnişin toprak üstü kısımlarının etanollü ekstrelerinin antienflamatuvar özellikleri, olası etki mekanizmaları incelenmiş ve kişniş yaprakları ile saplarının NO ve prostaglandin üretimini azalttığı gözlenmiştir (73). Özbek ve arkadaşlarının yaptığı bir çalışmada, kişniş uçucu yağ ekstresinin farelerde LD 50 dozu düzeyinin 2,257 mL/kg olarak hesaplandığı, sıçanlarda Carrageenan'la oluşturulmuş sağ arka pençe ödemi modelinde indometazinden daha zayıf bir antienflamatuvar aktivite gösterdiği ve bu etkinin uçucu yağı oluşturan komponentlerden en az ikisi tarafından meydana getirildiği bildirilmiştir (74).…”
Section: Antienflamatuvar Etkiunclassified
“…The overproduction of inflammatory mediators can lead to complications such as septic shock, cancer, diabetes, atherosclerosis, and obesity (13). NO and prostaglandin E 2 are produced by activation of iNOS and COX-2, respectively.…”
Section: 한국식품과학회지 제 48 권 제 6 호 (2016)mentioning
confidence: 99%
“…9 Previous studies reported that leaves of CS decreased lipopolysaccharide-induced nitric oxide (NO) production and had a NO scavenging effect in RAW 264.7 macrophages. 10 Moreover, it has anti-inflammatory potential in ultraviolet erythema and antioxidant effects in rats fed a high-fat diet. 11 Furthermore, we previously demonstrated that linoleic acid and linolenic acid in CS protect human skin keratinocytes against H 2 O 2 -induced oxidative damage, possibly by regulating antioxidative defense enzymes such as heme oxygenase-1 (HO-1) and total glutathione (GSH) through nuclear factor erythroid-derived 2-related factor 2.…”
Section: Introductionmentioning
confidence: 99%